Locked up and locked out?: the impact of imprisonment on labour market attachment - Bäckman, Olof (The British journal of criminology, 2018)
This article investigates what effects a first prison sentence has on labour market inclusion, both by comparing those sentenced to prison to the population as a whole, and by comparing groups of convicted offenders. We utilize longitudinal data on criminal sanctions and earnings available for two complete birth cohorts of Swedish men (N = 107,337). These data enable us to compare the labour market attachment of prison inmates both before and after imprisonment. Results from propensity score matching show small negative effects of imprisonment on post-release labour market attachment. Moreover, we find no effect for those without pre-sentence labour market attachment. Thus, the negative effects are restricted to those with some labour market attachment before imprisonment.